Impact of airport green atmospherics on mental health value, image, and loyalty among visitors and workers. (27th January 2020) - Han, Heesup; Olya, Hossein G.T.; Untaru, Elena‐Nicoleta; Ispas, Ana; Kim, Jinkyung Jenny; Kim, Wansoo
Abstract: Nature‐based solutions (NBS) are becoming increasingly crucial as NBS brings diverse health‐related benefits to travelers and workers in the tourism business sector. This research explored the influence of green atmospherics as NBS on airport occupants' mental health value, image, and loyalty generation processes. A quantitative approach with a field survey method was employed. A structural equation modeling and metric invariance test were used as data analysis technique. Our empirical result revealed that green atmospherics as NBS significantly improve the occupants' mental health value and image of the airport, and these variables contribute to their loyalty enhancement for the airport. The effect of green spaces and natural surroundings on loyalty was maximized through mental health value and image. In addition, the linkages from natural surroundings to mental health value and image were stronger in the visitor group whereas the mental health value—loyalty relation was stronger in the worker group.